Ekonometryczna analiza zależności między rozwojem regionalnym a gospodarką opartą na wiedzy - Strahl, Danuta; Bal-Domańska, Beata (Econometric Analysis of Interdependencies between Regional Development and Knowledge-based Econmy, 2008)
Knowledge is the most valuable resource facilitating the development of modern economies. Countries and regions capable of generating knowledge and technology, as well as their absorption and commercial implementation, present the biggest developmental potential. The article takes up an attempt of measuring interdependencies between regional development expressed in GDP per capita and innovation presented as the share of tertiary education graduates in an overall number of employees in the European NUTS-2 level regions. In order to measure the above relations, models for panel data were used and supported by the due estimation techniques. As it results from the conducted analysis, the level of regional development is directly related to the level of its inhabitant's education. The regions which achieved the highest level of development are: Luxemburg, Austria, Italy, Ireland. Following the same assumption the lowest level of regional development is presented by Latvia, Lithuania, Estonia, and Poland. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 45-54